The international monetary system after the financial crisis - Ettore Dorrucci; Julie McKay (European Central Bank (ECB), 2011)
The main strength of today's international monetary system – its flexibility and adaptability to the different needs of its users – can also become its weakness, as it may contribute to unsustainable growth models and imbalances. The global financial crisis has shown that the system cannot afford a benign neglect of the global public good of external stability, and that multilateral institutions and fora such as the IMF and the G20 need to take the initiative to set incentives for systemically important economies to address real and financial imbalances which impair stability. We draw this core conclusion from a systematic review of the literature on the current international monetary system, in particular its functioning and vulnerabilities prior to the global financial crisis. Drawing from this analysis, we assess the existing and potential avenues, driven partly by policy initiatives and partly by market forces, through which the system may be improved.
Keywords: C21; C51; G15; G21; G28; 330; financial globalisation; global imbalances; international liquidity; international monetary system; Internationales Währungssystem; Währungsreserven; Internationaler Finanzmarkt; Finanzkrise; Wechselkurs; Sonderziehungsrechte; G20-Staaten